TINGKAT PENYINTASAN Lithocarpus celebensis DI TAMAN HUTAN RAYA GUNUNG TUMPA - Jecson Kumeser Msen; Johny S. asirin; Hard Napoleon Pollo (COCOS, 2022)
Abstrak This study aims to determine the survival rate of Lithocarpus celebensis in the Great Forest Park (TAHURA) Gunung Tumpa H.V. people. The research was carried out on December 17 to December 21, 2021. In collecting data on the survival rate of Lithocarpus celebensis, it was divided into two stages, namely: 1. Observing the entire area of the Gunung Tumpa Forest Park with the help of grids measuring 1 ha to ensure that no areas were damaged. not observed, and then the plants obtained will be measured stem and tree height to obtain the number of individuals from seedlings, weaning, poles, and trees. The tree to be obtained is given a point or coordinates. The results obtained in the Mount Tumpa area stated that the distribution of Lithocarpus celebensis was spread in clusters, in the Gunung Tumpa Forest Park there were 82 individuals of Lithocarpus celebensis found from all areas of the Mount Tumpa area. Lithocarpus celebensis .scattered throughout the Mount Tumpa area with an altitude of 500 to 620 above sea level. It is known that the survival rate of Lithocarpus celebensis in Tahura Gunung Tumpa is very low due to low availability of youth, from 16 stems/100 ha out of a total tree density of 8 stems/100 ha. The number of individuals with the smallest diameter or population successor regeneration (<18.9 cm) reached more than 79% of the Lithocarpus celebicus population in Mount Tumpa. in other words, the presence of youth is much higher than the parent tree (diameter > 55.7 cm). Concerns about the survival rate can arise because the presence of trees in the next diameter class (18.9-55.6 cm) is very low, which is only 10% of the total population